CHANGES IN THE PATTERN OF RELIGIOUS UNDERSTANDING BETWEEN ISLAMIC COMMUNITIES OF MODERATE GROUPS AND RADICAL GROUPS - Khairul Izham (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
The understanding of religion is a dimension of belief or ideological belief, a dimension of religious practice or ritualistic, a dimension of experience or an experiential dimension of religious knowledge or intellectual and consequential. The purpose of this writing is the purpose of this writing is to understand religious understanding, how the pattern of understanding of moderate groups and how of understanding of radical groups. The method used was research in a literature journal. The conclusion of Islam does not view all religions as equal but treats all religions as equal, and it conforms to the concepts of Islam: egalitarian or does not discriminate against other religions. And as for the moderate carprogram, it is the first that the concept of 'tolerance' (tolerance), in accordance with the above moderate characteristics of Islam can be established if Indonesian muslims are already coexisting and mutually tolerant, will maintain stability between religious and religious harmony.